Contextual determinants of parental reflective functioning: Children with autism versus their typically developing siblings. (August 2020) - Enav, Yael; Erhard-Weiss, Dana; Goldenberg, Amit; Knudston, Marguerite; Hardan, Antonio Y; Gross, James J
Parental reflective functioning is defined as holding in mind one's child's thoughts, feelings, beliefs, and intentions and reflecting on how these mental states may be affecting the child's behavior. Although parental reflective functioning is often treated as a stable feature of the parent, there is growing appreciation that it may be shaped by the context in which the parent is operating. In this study, we examined parental reflective functioning using the Parental Developmental Interview when parents were talking about their interactions with their child with autism versus the child's typically developing siblings. Our sample included 30 parents who had a child between the ages of 3 and 18 years with a clinical diagnosis of autism spectrum disorder and at least one typically developing child. Findings indicated that parents exhibited significantly higher reflective functioning when interacting with their child with autism spectrum disorder versus the typically developing siblings, and the difference was moderated by parental self-efficacy. The evidence for a disparity in parental reflective functioning between children with autism spectrum disorder and their typically developing siblings (especially for parents with low parental self-efficacy) warrants further investigations that might lead to the development of effective interventions. Lay Abstract: In this study, we examined parental reflective functioning using the Parental Developmental Interview when parents were talking about their interactions with their child with autism versus the child's typically developing siblings. Our sample included 30 parents who had a child between the ages of 3 and 18 years with a clinical diagnosis of autism spectrum disorder and at least one typically developing child. Findings indicated that parents exhibited significantly higher reflective functioning when interacting with their child with autism spectrum disorder versus the typically developing siblings, and the difference was moderated by parental self-efficacy.